Factors Affecting the Utilization of Antenatal Care Service among Mothers Having Under 2 Years Children - Shahi, Raj Kumar; Poudyal, Jiwan; Upadhyay, Hari Prasad; Parajuli, Sumitra; Sedain, Prativa (International Journal of Silkroad Institute of Research and Training, 2023)
Background: The Antenatal care period is the time between immediately conceptions after to before birth baby. The objective of this research is to find out factor associated with ANC service utilization by mothers. Methods: Community based analytical cross sectional study was conducted in Junichande rural municipality, Jajarkot among mother have child under two years of age data is collected through interview method. Descriptive analysis and chi- square test were performed. Results: This study shows more than half of the (58.8%) mother had completed ANC. Ethnicity, education level, husband occupation, availability of essential drugs and equipment, satisfaction behavior of health worker and proper physical infrastructure are the factors that influence the ANC care utilization which were found significantly associated with ANC utilization. The main reason for not receiving ANC among mother were lack of awareness. Conclusions: This study suggest health care providers and policy maker to make aware mothers on maternal complication to prevent and neonatal mortality and increase ANC utilization.